Pandangan Gen Z Terhadap Live Music Yang Menambah Minat Konsumen Coffee Shop Di Kota Solo - Muhammad Annang Fahmi Roziq; Syahri Romadhon; Rayhan Gunaningrat (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
This study aims to determine Generation Z's views on live music that increases consumer interest in coffee shops in Solo. This research uses the Grounded Theory method, which is qualitative research that aims to develop theory from empirical data directly without any prior theory or hypothesis. Semi-structured interviews were conducted with several Gen Z in one of Solo's coffee shops. The results of the interviews with Gen Z show the complexity of views on live music in coffee shops. The existence of live music can increase the attractiveness of coffee shops. Experience, identity, sensation seeking and peer influence play an important role in attracting coffee shop consumers.